Long-Term Effect of Silicone Oil Tamponade for Postoperative and Posttraumatic Bacterial Endophthalmitis. (1st February 2021) - Kang, Yong Koo; Shin, Jae Pil; Park, Han Sang
Abstract : Purpose . To compare clinical features and microbial profiles, treatment outcomes, and prognostic factors of the eyes between postoperative and posttraumatic bacterial endophthalmitis after pars plana vitrectomy (PPV) with silicone oil (SO) tamponade. Methods . Overall, 57 eyes of 57 patients who diagnosed exogenous bacterial endophthalmitis and underwent PPV with SO tamponade between 2000 and 2019 were reviewed. Causative microorganisms, culture positivity, change of mean best-corrected visual acuity (BCVA), and course of treatment were investigated between postoperative and posttraumatic groups, and relevant factors were analyzed according to the final BCVA. Results . The mean BCVA change was not significantly different between groups. The positive rate of microorganisms was significantly higher in the postoperative group. The mean time to surgery over 48 hours, initial BCVA worse than hand motion, and additional surgery after initial vitrectomy were correlated with poor final BCVA worse than 20/200. There was significantly achieved final BCVA 20/200 or better in the Staphylococcus and Streptococcus group than the Enterococcus and Pseudomonas group. Conclusion . PPV with SO tamponade may be an effective surgical treatment strategy for exogenous bacterial endophthalmitis. Final visual outcomes were not significantly different between postoperative and posttraumatic groups, and the mean time to surgery, initial visual acuity, additional surgery, and type of microorganism are significantly related to visual prognosis.